Socioeconomic assessment of the current agronomic practices in Nigeria: case study of rice for the Atafi-Agro Use Case - Arouna, A.; Aboudou, R.; Ibrahim, A. (Africa Rice Center, 2024)
This report presents a socioeconomic assessment of the current rice agronomy practices in Nigeria, covering 1,440 households across the Kano, Jigawa, and Nasarawa states. The analysis showed that the rice farmers had a mean age of 45 years, with an average household size of nine members. Most household heads (98.75%) were male, predominantly in monogamous marriages (69.83%), and 84.44% had received a formal education. Farming was the primary occupation for 98.96% of the household heads. The survey highlighted significant food security challenges, with a high proportion of households experiencing food shortages, concerns regarding insufficient food, and limited access to nutritious options. Jigawa and Nasarawa were particularly affected by food insecurity. Agronomic practices vary across states with differences in input usage, irrigation practices, and crop management. The regression analysis identified key factors influencing rice production, including cultivated areas, farmer education, irrigation.